2005
DOI: 10.1681/asn.2005010039
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Ghrelin Enhances Acute Food Intake in Malnourished Patients Who Receive Maintenance Peritoneal Dialysis

Abstract: Anorexia and malnutrition confer significant morbidity and mortality to patients with end-stage kidney disease but are resistant to therapy. The aim of this study was to determine whether subcutaneous administration of ghrelin, an appetitestimulating gut hormone, could enhance food intake in patients who are receiving maintenance peritoneal dialysis and have evidence of malnutrition. The principal outcome measure was energy intake during a measured study meal. Secondary outcome measures were BP and heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(117 citation statements)
references
References 42 publications
2
111
1
1
Order By: Relevance
“…Ghrelin has potent orexigenic activity and induces an increase in food intake, and muscle mass with a positive change in energy uremic balance in rats (32)(33)(34). Ghrelin administered to dialysis patients increased appetite and food intake, induced a sustained positive change in energy balance (35,36) and increased food intake in malnourished patients on peritoneal dialysis (35). Thus, a decrease in AG in CKD could theoretically play a role in the malnutrition observed in many of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin has potent orexigenic activity and induces an increase in food intake, and muscle mass with a positive change in energy uremic balance in rats (32)(33)(34). Ghrelin administered to dialysis patients increased appetite and food intake, induced a sustained positive change in energy balance (35,36) and increased food intake in malnourished patients on peritoneal dialysis (35). Thus, a decrease in AG in CKD could theoretically play a role in the malnutrition observed in many of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate increase in energy intake in those patients was followed by a trend toward increased energy intake over the following 24 hours. In addition, there was no subsequent compensatory reduction in energy intake over the following 3 days, which would negate any potential therapeutic benefit of subcutaneous ghrelin administration [65].…”
Section: Ghrelin In Ckdmentioning
confidence: 99%
“…Ghrelin is an orexigenic peptide released primarily from the stomach; it increases appetite and adjusts both short-and long-term energy balance, making it a good candidate for treatment of anorexic patients with ESRD. Two pilot studies suggested improved energy intake during short-term ghrelin administration (72,73). There is also limited but supportive evidence for the effectiveness of pre-and probiotics on reducing plasma levels of some uremic toxins (74).…”
Section: Summary and Recommendationsmentioning
confidence: 99%